A Challenging Case of Hepatoblastoma Concomitant with Autosomal Recessive Polycystic Kidney Disease and Caroli Syndrome—Review of the Literature - Kadakia, Nevil; Lobritto, Steven J.; Ovchinsky, Nadia; Remotti, Helen E.; Yamashiro, Darrell J.; Emond, Jean C.; Martinez, Mercedes (Frontiers in Pediatrics, 2017)
We report a rare case of an 18-month-old female with autosomal recessive polycystic kidney disease, Caroli syndrome and pure fetal type hepatoblastoma. The liver tumor was surgically resected with no chemotherapy given. Now nine years post resection she demonstrates no local or distant recurrence and stable renal function.